1998
DOI: 10.1002/(sici)1097-4652(199803)174:3<370::aid-jcp11>3.0.co;2-d
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen peroxide-induced cytoskeletal rearrangement in cultured pulmonary endothelial cells

Abstract: Although the signaling pathways leading to hydrogen peroxide (H2O2)-induced endothelial monolayer permeability remain ambiguous, cytoskeletal proteins are known to be essential for maintaining endothelial integrity and regulating solute flux through the monolayer. We have recently demonstrated that thrombin-induced actin reorganization in bovine pulmonary artery endothelial cells (BPAEC) requires activation of both myosin light chain kinase (MLCK) and protein kinase C (PKC). Therefore, the present study was de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
71
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(78 citation statements)
references
References 36 publications
7
71
0
Order By: Relevance
“…Permeability increasing mediators such as thrombin, histamine, and H 2 O 2 enhance MLC phosphorylation, which precedes the onset of endothelial contraction (Fig. 10) (303,387,470). The myosin phosphorylation in the endothelial cells is regulated by two enzymes: nonmuscle MLCK and myosinassociated protein phosphatase.…”
Section: B Myosin Light Chain Kinasementioning
confidence: 96%
See 2 more Smart Citations
“…Permeability increasing mediators such as thrombin, histamine, and H 2 O 2 enhance MLC phosphorylation, which precedes the onset of endothelial contraction (Fig. 10) (303,387,470). The myosin phosphorylation in the endothelial cells is regulated by two enzymes: nonmuscle MLCK and myosinassociated protein phosphatase.…”
Section: B Myosin Light Chain Kinasementioning
confidence: 96%
“…Activated MLCK directly phosphorylates MLC at Thr-18 and Ser-19 site, which induced isometric tension development and actin polymerization in endothelial cells (136). Zhao et al (470) reported that H 2 O 2 also induced MLC phosphorylation in endothelial cells. Though the inhibition of MLCK blocked H 2 O 2 -induced MLC phosphorylation, yet it did not affect H 2 O 2 -induced actin and myosin assembly.…”
Section: B Myosin Light Chain Kinasementioning
confidence: 99%
See 1 more Smart Citation
“…Two Ca 2ϩ /calmodulin-dependent enzymes known to be activated by H 2 O 2 , the myosin light chain kinase (MLCK), and CaMKII, have also been found to regulate VRACs (20,27,49,50). We therefore explored whether changes in intracellular Ca 2ϩ and the activation of Ca 2ϩ /calmodulin-dependent enzymes are involved in the H 2 O 2 effect.…”
Section: Hydrogen Peroxide Potentiatesmentioning
confidence: 97%
“…High levels of exogenous oxidants increase recruitment of actin to the cytoskeleton, and conversely actin cytoskeletal disruption precipitates oxidant-dependent NF-␤ activation (8,9). Oxidant production is also most prominent in actively migrating endothelial cells at the margin of a monolayer wound and, in particular, is concentrated in membrane ruffles of these highly motile cells (10).…”
mentioning
confidence: 99%